The Touristic Potential of Aral Sea and an Innovative Approach in its Effective - Rashidov Rustamjon Sharof (Indonesian Journal of Cultural and Community Development, 2020)
The article mainly illustrates Aral Sea as one of the largest man-made environmental devastation and provides eligible programs that aims at remedying humanity mistake partially through converting the disastrous territory into an eco-touristic destination. Together with exploring adverse impacts of Aral Sea on the locals, the study also examines attractiveness and touristic potential of the territory which will then leads creating an attractive image of the land to ensure a surge of foreign investment. This is the strategic thinking that can reform the prospective revenue generated by the use of Aral Sea as a tourist destination. Based on the identified problems and examined potentiality, the prospects for the further development of integration processes focused on the effective use of the area will be determined.